Environmental Microzonification of Solid Waste in the New City District - Lazo Ramos, Richard Sabino (2020)
The purpose of this research is to characterize the solid waste, to elaborate a microzonification of the places where the habitants improperly dispose the waste coming from the construction and demolition, as well as to propose an optimal design of a new truck route for the collection of garbage in the district of Ciudad Nueva.  He study was carried out in the months of September and October of 2017, in which the procedure of the methodological guide was applied for the development of the municipal solid waste characterization study, in which a solid waste composition of 53.72% was obtained corresponding to organic waste, 5.89% cardboard, 5.44% paper, 5.39% bags and 3.64% PET plastic, among others. Ninety-seven disposal points for construction and demolition waste were micro-zoned by the sweeping method by the different sectors of the district with the help of the GPS (Global Position System) instrument. And finally, with the Autocad tool, a new solid waste collection route was designed for garbage compactor trucks, in which it was reduced from 124.710 km per day to 49.592 km optimizing fuel consumption from 20 gallons to 6.50 gallons per day, minimizing the emanation of greenhouse gases that is a contributor to climate change, in addition to economically generating savings in fuel costs. In this way, the present study will contribute to the improvement of environmental management, constituting the starting point for the future design of plans and strategies to be adopted by the Ciudad Nueva District Municipality.